Sebaran Tembikar Di Trowulan: Hasil Survei IFSA 1991-1993 - Mindra Faizaliskandiar (Balai Arkeologi Yogyakarta, 1995)
It should be acknowledged that the validity and reliability of the archaeological remains on the surface of the Trowulan Site as systematic survey research data is still in doubt, because the taphonomic process that has taken place in the last few decades, mainly due to wild and negative human activity at this site, has been going on intensively in a relatively long period of time. However, such research should still be held at the Trowulan Site to meet the standard of spatial research procedures (spatial archeology). The results of this study will establish empirically the level of confidence of the surface data, and possibly those under the soil of the Trowulan Site.